Effect of alkalis on products of enforced carbonation of cement paste. (12th July 2021) - Zajac, Maciej; Skibsted, Jørgen; Durdzinski, Pawel; Ben Haha, Mohsen
Highlights: Effect of alkalis on the carbonation reaction products is investigated. Carbonation products are stable at a wide range of pH. Alkalis influence the size of the calcite crystals. Alkalis modify the structure of the alumina-silica gel. Alkalis have strong impact of sulfate leaching during carbonation. Abstract: An approach based on enforced, wet carbonation of cement fines obtained from recycled concrete and its application as an SCM in new composite cements is presented as a new carbon capture and utilization technology. While the carbonation products are stable at a wide range of conditions, it is found that alkalis have a strong impact on product properties, as shown by carbonation in NaOH solutions in this study. Calcium carbonate precipitates mainly as calcite, regardless of the alkali concentration, however, the alkalis influence the size of the calcite crystals, which are smaller at low alkali concentrations. Alkalis modify also the structure of the alumina-silica gel, as a result of absorption of either sodium or calcium ions in this phase. Furthermore, alkali ions present in the solution influence directly the sulphate content of the carbonated cement paste, since a higher alkali concentration in the solution promotes leaching of sulphate.